(untitled) (Ustozlar uchun, 2026)
This article examines psychological and mystical realism in British and Uzbek literature through the lens of cognitive literary studies. Moving beyond descriptive interpretations of interiority and spirituality, the study argues that both modes operate as structured simulations of consciousness. Drawing on cognitive narratology, Theory of Mind, and narrative simulation theory, the paper demonstrates how selected British and Uzbek prose texts construct inner speech, reconstructive memory, and moments of intensified perception. The analysis reveals that psychological and mystical realism share underlying cognitive mechanisms, while cultural traditions shape their ethical and symbolic configurations. The study contributes to comparative literary scholarship by introducing a cognitive framework to analyze cross-cultural representations of inner experience.